ABA-induced active stomatal closure in bulb scales of Lanzhou lily - Lei Gong; Hai-Qing Liu; Ye Hua; Ya-Yun Zhang; Md. Mahadi Hasan (Plant Signaling & Behavior)
Abscisic acid (ABA) mediated stomatal closure is a highly effective mode of active stomatal regulation under drought stress. Previous studies on stomatal regulation have primarily focused on the leaves of vascular plants, while research on the stomatal behavior of bulbous plants remains unknown. In addition, ABA-induced stomatal regulation in bulbs has yet to be explored. Therefore, we aim to investigate the ABA-induced active regulation in the bulb of the Lanzhou lily (Lilium davidii var. unicolor). The morphological characteristics of epidermal strips were analyzed along with a stomatal aperture assay to investigate the bulb's stomatal response to ABA. Moreover, the mechanism of ABA signaling was explored using treatments with ABA signaling chemicals and corresponding scavengers. This study revealed that stomata are mainly distributed on the upper part and outer surface of the bulb. The guard cells of the lily bulb are inflated, and the stomata have a nearly circular shape with relatively low stomatal density. Exogenous ABA was found to induce varying degrees of stomatal closure in a dose-dependent manner, with significant stomatal aperture reduction observed after treatment with 10 µM ABA. Overall, the study indicated that both hydrogen peroxide (H2O2) and nitric oxide (NO) are involved in the ABA-induced stomatal closure process, with H2O2 functioning as an upstream component of NO.